2015
DOI: 10.4012/dmj.2015-095
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of gingival connective tissue responses to 3-dimensional collagen nanofiber-coated dental implants

Abstract: The aim of the present study was to evaluate the gingival connective tissue response to screw-type titanium implants coated with Type I collagen nanofibers, which were prepared using the electrospray deposition method. Implants were immediately inserted into the socket of maxillary first molars after the extraction. Undecalcified sections after 4 weeks implantation were histologically observed. Better contact of the gingival connective tissue was generally observed around the collagen nanofiber-coated implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Interestingly, those fiber groups had perpendicular rod-like attachments with the implant surfaces at intervals of 30 m (asterisks in Fig. 12b and c), similar to the characteristic morphology seen in the gingiva and periodontal ligaments of natural teeth 11) . Such rod-like attachments were not observed in the Laser-Ti and Coll/Laser-Ti implants at 3 weeks.…”
Section: Histological Evaluation Of Gingival Connective Tissue In Ratmentioning
confidence: 77%
See 4 more Smart Citations
“…Interestingly, those fiber groups had perpendicular rod-like attachments with the implant surfaces at intervals of 30 m (asterisks in Fig. 12b and c), similar to the characteristic morphology seen in the gingiva and periodontal ligaments of natural teeth 11) . Such rod-like attachments were not observed in the Laser-Ti and Coll/Laser-Ti implants at 3 weeks.…”
Section: Histological Evaluation Of Gingival Connective Tissue In Ratmentioning
confidence: 77%
“…In our present study, collagen immobilization did not enhance attachment of gingival connective tissue compared with the LaserTi implants. Raita et al reported that three-dimensional collagen nanofiber structures were more effective for gingival connective tissue attachment than two-dimensional collagen immobilization 11) . Atsuta et al showed that laminin-5 contributed to attachment of the peri-implant epithelium to the titanium implant surface 32) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations